2004
DOI: 10.1177/000331970405500408
|View full text |Cite
|
Sign up to set email alerts
|

Intima-Media Thickness and Arterial Distensibility in Behçet’s Disease

Abstract: The etiology of Behçet's disease, a systemic vasculitis, is unknown. Vascular involvement may be seen in 25% of patients with Behçet's disease. Vasculitis make the prognosis of Behçet's disease severe. The aim of this study is to examine the structural and functional changes and relations of these changes with progression and prognosis of Behçet's disease. For this purpose, 40 patients with Behçet's disease and 40 healthy volunteer control subjects were analyzed, additionally patients with Behçet's disease wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
47
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 24 publications
7
47
0
1
Order By: Relevance
“…cIMT has been reported to be high in some studies on BD (13,(25)(26)(27)(28). However, this high value has not been detected in other studies (14, 29-31).…”
Section: Discussionmentioning
confidence: 99%
“…cIMT has been reported to be high in some studies on BD (13,(25)(26)(27)(28). However, this high value has not been detected in other studies (14, 29-31).…”
Section: Discussionmentioning
confidence: 99%
“…[9] The use of noninvasive parameters such as IMT may be useful in defining disease progression and identifying BD subjects at high risk. [10] The data from patients with active BD may be compatible with the serum lipid profile, which is accepted as a risk for the development of atherothrombosis. [11] Dyslipidemia, especially in the form of hypertriglyceridemia, might be a risk factor and has proven to be the best marker for the occurrence of thrombosis in patients with BD.…”
mentioning
confidence: 90%
“…[3][4][5][6][17][18][19] Previous studies have reported a predisposition toward the development of atherosclerosis in BD, [8][9][10] and in these disease states, hardening of the arteries generally occurs at a younger age. [3][4][5][6] Many changes occur in the arterial wall before the clinical findings of atherosclerotic diseases become evident.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][21][22][23][24][25][26] Increased values of IMT with BD have been reported in some studies. [7][8][9] Alan et al [8] also proved the existence of decreased arterial distensibility in BD, and Rhee et al [22] detected increased arterial stiffness in BD. Akçar et al [26] reported lower peak systolic and end-diastolic flow velocities throughout internal carotid artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation